Clinical Significance of Molecular Expression Profiles of Hürthle Cell Tumors of the Thyroid Gland Analyzed Via Tissue Microarrays - Hoos, A. (Institutional Knowledge at Singapore Management University, 2002)
Hürthle cell tumors are rare thyroid neoplasms for which disease biology is poorly understood and diagnosis of carcinoma can be challenging. The aim of the study was to characterize molecular expression profiles of Hürthle cell tumors and to determine the clinical significance of identified phenotypes. Paraffin-embedded tissue cores of normal thyroid (n = 18), and histopathologically well-defined Hürthle cell adenomas (n = 27), Hürthle cell tumors of unknown malignant behavior (n = 7), and minimally (n = 14) and widely (n = 21) invasive Hürthle cell carcinomas were arrayed in triplicate on tissue microarrays. Expression profiles of p53, mdm-2, p21, Bcl-2, cyclin D1, and Ki-67 were detected by immunohistochemistry and correlated with clinicopathological data and patient outcome using standard statistical methodology. Median follow-up time was 8 years. High Ki-67 proliferative index was evident only in the clinically aggressive widely invasive Hürthle cell carcinomas and was associated with significantly reduced relapse-free (P = 0.001) and disease-specific (P < 0.001) survival. The molecular phenotype of Hürthle cell tumors, independent of histopathological subtype diagnosis, was characterized by p53(?), mdm-2(+), p21(±), cyclin D1(?), and Bcl-2(±). Normal thyroid tissue demonstrated a p53(?), mdm-2(?), p21(?), cyclin D1(?), and Bcl-2(+) phenotype. The Bcl-2(+) phenotype was associated with improved relapse-free survival (P = 0.04) and disease-specific survival (P = 0.01) in widely invasive carcinomas and the Ki-67(+)/Bcl-2(?) phenotype was associated with the diagnosis of widely invasive Hürthle cell carcinoma (P < 0.001). This study demonstrates that tissue microarray-based profiling allows identification of molecular markers that are associated with patient prognosis. High Ki-67 proliferative index was associated with adverse outcome in Hürthle cell neoplasms. Together with down-regulation of Bcl-2, high Ki-67 proliferative index may be useful for diagnosing widely invasive Hürthle cell carcinomas. Molecular alterations in the p53 pathway play a role in Hürthle cell tumorigenesis, but other unidentified molecular changes seem to be required to induce the malignant phenotype.